УЛЬТРАЗВУКОВІ РІВНЕМІРИ З КОРЕКЦІЄЮ ТЕМПЕРАТУРНИХ ПОХИБОК З НИЖНІМ РОЗМІЩЕННЯМ ВИПРОМІНЮВАЧІВ - Саволюк, О.М.; Новік, А.І. (Інститут електродинаміки Національної академії наук України, 2017)
This article deals with the temperature error correction in ultrasonic level gauges using special sensor designs located in the lower part of the tanks. It is shown that there is a possibility of temperature error correction depending on temperature variation of the environment throughout the tank height. References 10, figures 3, table.